2017
DOI: 10.1536/ihj.16-327
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Servo-Ventilation Treatment Increases Stroke Volume in Stable Systolic Heart Failure Patients With Low Tricuspid Annular Plane Systolic Excursion

Abstract: SummaryWe hypothesized that the effects of adaptive servo-ventilation (ASV) therapy were influenced by right-sided heart performance. This study aimed to clarify the interaction between the effects of ASV and right-sided heart performance in patients with stable heart failure (HF) with reduced ejection fraction (HFrEF).Twenty-six stable HF inpatients (left ventricular ejection fraction < 0.45, without moderate to severe mitral regurgitation (MR) were analyzed. Echocardiography was performed before and after 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…3) As a functional index, reduced tricuspid annular plane systolic excursion was associated with an increase in systolic volume during ASV support. 4) The authors hypothesized that improvement in RV function due to the unloading of preload on the RV also improved left ventricular diastolic performance via a rightleft heart morphological interaction. As a pressure index, our team reported that an elevated baseline RV enddiastolic pressure was a key to increase CO during ASV support.…”
Section: To the Editormentioning
confidence: 99%
“…3) As a functional index, reduced tricuspid annular plane systolic excursion was associated with an increase in systolic volume during ASV support. 4) The authors hypothesized that improvement in RV function due to the unloading of preload on the RV also improved left ventricular diastolic performance via a rightleft heart morphological interaction. As a pressure index, our team reported that an elevated baseline RV enddiastolic pressure was a key to increase CO during ASV support.…”
Section: To the Editormentioning
confidence: 99%
“…12) These acute effects are observed during 10-30 minute ASV support. [12][13][14][15] Such effect reduces volume and pressure loads in the left ventricular (LV) cavity, which facilitates LV reverse remodeling, accompanied by decrease in plasma level of B-type natriuretic peptide (BNP) and E/e', recovery of the degree of mitral regurgitation, improvement in LV ejection fraction (LVEF), and reduction in LV volume after several months of ASV support. 13,[16][17][18][19][20] Not only the hemodynamic stabilization but also the stabilization of respiratory pattern results in the suppression of sympathetic nerve activity.…”
Section: Efficacy Of Asv Therapy Shown In a Single-centermentioning
confidence: 99%
“…37) The lower tricuspid annular plane systolic excursion and enlarged RV cavity were reported as predictors of improvement in CO during ASV support. 15,36) Both parameters indicate RV dysfunction, which was improved following an increase in CO during ASV support. The authors speculated the mechanism as follows: the recovery of RV dysfunction during ASV support also improves LV diastolic dysfunction and increases CO via a geometric shift in the interventricular septum.…”
Section: Optimal Patient Selectionmentioning
confidence: 99%